2012
DOI: 10.1038/ejcn.2012.28
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial platelet aggregation: effects of different meals and glycemic index

Abstract: BACKGROUND/OBJECTIVES: Hyperglycaemia is associated with increased platelet aggregation that increases the risk of thrombosis in people with type-2 diabetes and cardiovascular disease. Low glycemic index (GI) meals high in carbohydrate or moderately high in protein have been shown to acutely reduce postprandial excursions of plasma glucose and insulin compared with high carbohydrate high GI meals. However, it is not known whether these differences in glucose and insulin profile also impact on postprandial plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
2
8
0
1
Order By: Relevance
“…Impedimetric measurement detected similar, increased platelet adhesion in individuals with a history of allergic diseases. The association between blood glucose levels and platelet aggregability has already been described: Ahuja et al found decreased platelet aggregation in postprandial samples . We found a same negative correlation between platelet adhesion and blood glucose levels.…”
Section: Discussionsupporting
confidence: 89%
“…Impedimetric measurement detected similar, increased platelet adhesion in individuals with a history of allergic diseases. The association between blood glucose levels and platelet aggregability has already been described: Ahuja et al found decreased platelet aggregation in postprandial samples . We found a same negative correlation between platelet adhesion and blood glucose levels.…”
Section: Discussionsupporting
confidence: 89%
“…256 In healthy subjects, platelet aggregation is reduced postprandially, but this decrease differs little between meals of different GI, which induce different glucose and insulin responses. 257 The concepts of GI and GL have been accepted by the ADA 258 and by EASD 259 guidelines as a parameter to be taken into account when prescribing a diet for a diabetic patient.…”
Section: Glycemic Index (Gi) and Glmentioning
confidence: 99%
“…Moreover, it has been demonstrated that the anti-bacterial effect of PRP against Staphylococcus aureus, Staphylococcus epidermidis, Propionibacterium acnes and meticillin-resistant Staphylococcus aureus was not linked to the presence of leukocytes 18 . Finally, platelet activation is reduced postprandially 19 . Moreover, a gentle mastication is able to induce the release of pro-inflammatory components into the bloodstream, especially when patients have severe periodontal disease 20 .…”
Section: Therapeutic Protocolmentioning
confidence: 99%